2022
DOI: 10.1002/nbm.4751
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in the visual pathway of retinitis pigmentosa rats: A longitudinal multimodal magnetic resonance imaging study with histopathological validation

Abstract: Because retinitis pigmentosa (RP) has been shown to cause degenerative changes in the entire visual pathway, there is an urgent need to perform longitudinal assessments of RP‐induced degeneration and identify imaging protocols to detect this degeneration as early as possible. In this study, we assessed a transgenic rat model of RP by using complementary noninvasive magnetic resonance imaging techniques, namely, proton magnetic resonance spectroscopy (1H‐MRS), to investigate the metabolic changes in RP. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Thus, stimuli and sensory transduction also plays a role in RP progression, making photoreceptor cells and other neural cells susceptible to excitotoxic neurotransmitters, such as glutamate, or to the action of other neurotransmitters, like GABA or glycine [ 67 ]. As mentioned above, RP leads to a progressive loss of photoreceptor cells, but other neural cells suffer morphologic and metabolic changes resulting in retinal remodeling including loss of retinal ganglion cells (RGCs) or network rewiring [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stimuli and sensory transduction also plays a role in RP progression, making photoreceptor cells and other neural cells susceptible to excitotoxic neurotransmitters, such as glutamate, or to the action of other neurotransmitters, like GABA or glycine [ 67 ]. As mentioned above, RP leads to a progressive loss of photoreceptor cells, but other neural cells suffer morphologic and metabolic changes resulting in retinal remodeling including loss of retinal ganglion cells (RGCs) or network rewiring [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The visual cortex is one of the most important cortical structures in the brain and is primarily associated with the processing of visual information. Studies have revealed that eye disorders associated with retinal degeneration, including glaucoma [6], retinitis pigmentosa [7] and age-related macular degeneration [8], and systemic diseases, such as diabetes [9] and systemic lupus erythematosus [10] can trigger interactive structural and functional reorganisations of the visual cortex. The current therapeutic approaches for retinal degenerative diseases are limited and mainly aim to restore or substitute the retinal input.…”
Section: Small Animal Models Have Become Important Tools For Broadeni...mentioning
confidence: 99%